Explaining Waiting Times Variations for Elective Surgery Across OECD Countries - Siciliani, Luigi (OECD Health Working Papers, 2003)
Waiting times for elective surgery are a significant health policy concern in approximately half of all OECD countries. The main objectives of the OECD Waiting Times project were to: i) review policy initiatives to reduce waiting times in 12 OECD countries; and ii) to investigate the causes of variations in waiting times for non-emergency surgery across countries. The first objective was addressed in an earlier report (Hurst and Siciliani, 2003; OECD Health Working paper, n.6). This report is devoted to the second objective. An interesting feature of OECD countries is that while some countries report significant waiting, others do not. Waiting times are a serious health policy issue in the 12 countries involved in this project (Australia, Canada, Denmark, Finland, Ireland, Italy, Netherlands, New Zealand, Norway, Spain, Sweden, and the United Kingdom). Waiting times are not recorded administratively in a second group of countries ...